Comparison of Preoperative Endoanal Ultrasonography with Intraoperative Findings for Fistula In Ano - Subasinghe, Duminda; Samarasekera, Dharmabandhu N. (Springer-Verlag, 2010)
Background Fistula in ano is a common benign anal condition seen in surgical practice. If fistula anatomy is incorrectly delineated or an occult abscess is missed, there is a risk of incomplete healing, recurrence of the fistula, or even iatrogenic sphincter injury from surgery resulting in anal incontinence. Therefore, an imaging modality ideally would provide accurate information that can be used to delineate the tract(s) prior to surgery. The aim of this study was to determine the accuracy of endoanal ultrasonography (EAUS) during the preoperative assessment of anal fistula tracts in respect to the type of the fistula, horseshoeing of the tract, and localized collections. Methods A consecutive series of 64 patients underwent preoperative EAUS assessment of the fistula. All patients subsequently had surgical exploration under anesthesia irrespective of findings at sonography. The operative findings were compared with the US findings. The association between EAUS and operative findings was determined by nonparametric Spearman’s rank correlation (rho) coefficient test. Results The male/female ratio was 58:6. Mean age was 41.53 years (range 11–60 years). EAUS detected the fistula tract in most (95.3%). On EAUS, the primary tract was transsphincteric, intersphincteric, or superficial in 34 (53.1%), 25 (39.1%), and 2 (3.2%) patients, respectively. Localized collections were identified in 24 of the 64 (37.5%) patients (rho = 0.986). The fluid collection locations were 12 intersphincteric, 7 superficial, 4 infralevator, and 1 supralevator. At surgery, 38 (59.4%) fistula tracts were transsphincteric, 17 (26.6%) intersphincteric, 5 (7.8%) suprasphincteric, and 3 (4.7%) superficial. US correctly predicted the primary tract in 71.9% of fistulas (rho = 0.5). Conclusions EAUS has high accuracy for predicting the type of anal fistula and for detecting associated sepsis/fluid collections. This information is useful for preoperative planning of fistula treatment. EAUS therefore is an accurate test for determining fistula anatomy prior to surgery.